THU0445 Primary diagnosis of large vessel vasculitis by tissue histology after surgery of aortic valve and ascending aorta. (12th June 2018) - Assmann, G.; Karliova, I.; Langer, F.; Schreiber, M.; Pfreundschuh, M.; Schaefers, H.-J.
Abstract : Background: Large vessel vasculitis showed different histological patterns, ranging from well-formed granulomas and lymphoplasmacytic pattern to giant cell pattern. Most of entities of large vessel vasculitis belong to rheumatic diseases such as the giant cell arteritis (GCA). The clinical feature is very variable depending on the GCA manifestations. Objectives: Here we present an observation study of non-vasculitis patients, which had to undergo surgery of aortic valve and/or ascending aorta with a tissue histology of aortic inflammation. Methods: In the department of thoracic surgery of the University Medical School of Saarland, Germany, 1474 patients (in 2014 n=806, in 2015 n=668) underwent thoracic surgery of aortic valve or ascending aorta due to different indications such as any entity of aortic aneurysm, dissection, aortic stenosis and/or insufficiency. Patients with bacterial endocarditis were excluded from analysis. All surgical specimens were pathologically analysed according standard procedure. All specimens (n=19 in 2014, n=17 in 2015) with histological inflammation signs of aortitis being negative for tbc, mycosis, or lues were underwent further investigation searching for IgG4 +plasmacells, giant cells, and granuloma; all patients (n=36) were re-evaluated by a rheumatologist (immediately during the hospitalisation or within 3 weeks with outpatient presentation) including laboratory tests for RF, ANA, ANCA, ACCP, IgG subclasses, complement, ESR, CRP. Furthermore, all aortitis patients were investigated with MRI of aorta (n=15) or PET scan (n=17) or both (n=4) between 4 to 12 weeks after surgery to exclude persistent aortitis in native vessels. All patients which were diagnosed for aortitis through MRI and/or PET received immunosuppressive treatment containing glucocorticosteroids with or without synthetical or biological DMARDs. Results: Patients after thoracic surgery of aortic valve and/or ascending aorta were positive tested for aortitis in 2014 with the frequency of 2.36% (n=19/806) and in 2015 2.54% (n=17/668). The mean age of the 36 cases were 61 (range 39–80), of them were male 55.5% (n=20). The pathologic findings described 14 cases typical for GCA, 6 with granuloma, one with IgG4 +plasmacells, and one with predominant lymphocytic infiltration, 14 with unspecific inflammation. Rheumatologic consultation in all 36 cases could evaluated in 6 patients a preexisting rheumatologic disorder (RA n=2, polymyalgia rheumatica (PMR) n=4) without treatment. One patient were positive for significant elevated serum levels of IgG4. MRI and/or PET scan documented aortitis spots in the native aorta with or without concerning iliac arteries and/or supra-aortic vessels. All imaging-positive aortitis patients (n=12) were treated with glucocorticosteroids according to the protocol for giant cell arteritis (prednisolone 1 mg/Kg/body weight), six patients additionally with methotrexate, one with tocilizumab and one with rituximab. Conclusions: Only a small fraction of thoracic surgery patients with aortic aneurysm, dissection, aortic stenosis and/or insufficiency show histologic signs of aortitis. However, a third of them could be diagnosed via histological findings for active large vessel vasculitis after surgery. Disclosure of Interest: None declared